Gustiness in thermally-stratified urban turbulent boundary-layer flows and the influence of surface roughness. Issue 208 (January 2021) - Duan, G.; Takemi, T.
Abstract: Gustiness is examined for the wind speed, fluctuations, turbulence intensities and fluxes for a real urban topography. Using large-eddy simulation (LES) and an ensemble sampling approach, which allows a more comprehensive characterisation of the urban morphological features, a wide range of boundary-layer stabilities is considered: the bulk Richardson number, Rb ​∈ ​[−0.41, 0.82]. Ratios of the proposed gustiness statistics, G, over the conventional time-averaged flow and turbulence statistics are maximised for z / H ave ​≲ ​1 (where H ave is the mean building height). The strong linear scaling of G with the plan-area index ( λ p ) for neutral stratification is found to persist for stably- and unstably-stratified flows ( R 2 0.8). By contrast, the non-dimensionalised building-height variability, σ H / H ave, and the effective frontal-area index, λ f ^ ≡ λ f H a v e / σ H, are argued to be of more appropriateness as scaling parameters for G compared to their original forms, σ H and λ f . While the sensitivity of G to Rb is well defined at greater heights, the influence of surface inhomogeneity may be strong enough to oppose the effect of thermal stratification in the lower surface layers. Qualitative differences in the sensitivities to the boundary-layer stability are narrowly distinguishable amongst the zeroth-, first- and second-order gustiness statistics. The results are relevant to the understanding of urban wind hazards in thermally-stratified boundary layers. Highlights: The strong linear scaling of the gustiness statistics with the plan-area index persists for thermally-stratified flows. Ratios of the gustiness statistics over the conventional time-averaged flow and turbulence statistics attain the maxima within the canyons. An effective frontal-area index is argued to be of more appropriateness as a scaling parameter for the gustiness statistics. The proposed gustiness diagnostics exhibit substantially similar sensitivity to the boundary-layer stability.